Perbedaan Jumlah Basuhan dalam Berwudhu’: Studi Analisis terhadap Kitab Sharḥ Musnad al-Shāfiʿī - Samsir (Journal of Hadith Studies, 2021)
This study aims to identify and analyze the differences in the number of washes for the body parts involved in wudhu as described in Musnad al-Shāfi‘ī compared to other hadith collections. Wudhu is a significant act of worship in Islam, as it serves as a prerequisite for the validity of other acts of worship, such as salat. Without wudhu, such acts are considered invalid. However, there is a difference in the number of washes prescribed for the body parts in wudhu, which is the primary focus of this study. The method employed in this research is a qualitative approach using library research, in which data is collected through the study of various literature sources, including hadiths found in classical books and works by renowned scholars. The study results show that there are hadiths stating that washing the body parts involved in wudhu is obligatory only once, while the second and third washes are considered sunnah. This explanation is found in several prominent hadith collections, such as Sunan at-Tirmiżī, Ṣaḥīḥ al-Bukhārī, Sunan Abī Dāwud, Sunan an-Nasāʹī, Sunan Ibn Mājah, and Sunan ad-Dārimī. Therefore, washing the body parts involved in wudhu three times is not obligatory, as stated in Sharḥ Musnad al-Shāfi‘ī, which leans more towards explaining the practice as sunnah. This study is expected to provide a clearer insight into the differing views on the practice of wudhu in the hadith tradition